Sistem Kekerabatan dalam Budaya Minangkabau pada Antologi Cerpen Karya A.A Navis dan Implikasinya Terhadap Pembelajaran Apresiasi Sastra di SMA - Rahman, Irawati; Hendri, Bunga Febrimora (Department of Language and Literature, Faculty of Cultural Studies, Universitas Brawijaya, 2020)
AbstractThe aim of this research was to characterize the cultural values of Minangkabau in A Complete Anthology of the Short Stories of A.A. Navis and the implications of the research on the literature teaching at the Senior High School. This was a qualitative research focusing on content analysis. The contents analyzed related to the Minangkabau kinship system and social community. The descriptive method was used in this research. The object of the research was A.A. Navis's Comprehensive Short Stories Anthology. Based on the results of the research, the cultural values of Minangkabau have been revealed throughout the A.A Navis' Complete Anthology of Short Stories. Navis viewed as follows: (1) the relationship between mother and children, (2) the relationship between father and children, (3) the relationship between uncle and his nieces and nephews, (4) the relationship between children in law and parents in law, (5) the marriage in Minangkabau. The implication of this research in the reading class was: (1) expressing interesting things in the short story of thoughtdiscussion; (2) expressing cultural values in the short story of thought-discussion.Â AbstrakPenelitian ini bertujuan untuk mengkarakterisasi nilai-nilai budaya Minangkabau dalam Antologi Lengkap Cerpen A.A. Navis dan implikasi penelitian terhadap pembelajaran sastra di SMA. Ini adalah penelitian kualitatif yang berfokus pada analisis isi. Isi yang dianalisis terkait dengan sistem kekerabatan dan sosial kemasyarakatan Minangkabau. Metode deskriptif digunakan dalam penelitian ini. Objek penelitian adalah A.A. Antologi Cerita Pendek Komprehensif Navis. Berdasarkan hasil penelitian, nilai-nilai budaya Minangkabau yang terungkap dalam Antologi Cerpen Lengkap A.A Navis. Navis adalah sebagai berikut: (1) hubungan ibu dan anak, (2) hubungan ayah dan anak, (3) hubungan paman dan keponakan, (4) hubungan menantu dan orang tua dalam hukum, (5) perkawinan di Minangkabau. Implikasi dari penelitian ini di kelas membaca adalah: (1) mengungkapkan hal-hal yang menarik dalam cerpen diskusi pemikiran; (2) mengungkapkan nilai-nilai budaya dalam cerpen diskusi pemikiran.